The doctor-patient relationship - Héctor Rodriguez Silva (Centro Provincial de Información de Ciencias Médicas. Cienfuegos, 2010)
A review on specific aspects of the personal relationship among doctors, patients and their relatives through different epochs as well as the changes they have undergone is presented. Their characteristics and classifications are divided into active or passive, guided cooperation and mutual participation. Different stages and their importance as well as the most frequent deficiencies are detailed. Current situation in capitalist countries with neoliberal systems where health care is managed by private enterprises and insurances, and medical services are just another commercial activity is discussed. Finally, the impact of technological advances in present times is commented, both in its positive and negative aspects.